Modern Tourist Practices of the Northern and Arctic Territories - Arseniy A. Morozov (Арктика и Север)
The ideas of northern and Arctic tourism are relevant in the modern world. Currently, northern tourism is becoming more and more popular among people with medium and high incomes in different countries, including Russia, and the trend of its development is positive. The purpose of this study is to show the relevance of tourism development in the northern and Arctic territories, to identify current trends and the need of people for the development of such tourism. The Arctic is becoming an increasingly popular tourist destination. The increased interest in tourism in the Arctic has led to the creation of appropriate infrastructure and has had an impact on the region and the people who inhabit it. It has also impacted the cultural identity and traditional livelihoods of the region. In particular, the recent rapid growth of tourism and related activities will have a permanent impact on the environment and cultures of the Arctic. The article presents an analysis of modern research on this topic. The author’s research of ethnocultural tourism in the northern territories of the Karelian borderland is shown. Conclusions about the necessity of tourism development on the northern border territories and in the Arctic zones are made.